Populismo: un análisis histórico y comparado de Argentina, Brasil y Venezuela - Poblete Vásquez, Mario Eduardo (2016)
The phenomenon of populism is very difficult to grasp. However, in an academic sense, populism can be classified into two main criteria. In the historical-geographical field, it is possible to identify different categories of populism such as: the Russian agricultural populism of nardonik intellectuals; the Latin American populism that arose in the middle of the 20th Century and endures to the present time; and the so called neopopulism which started in Europe in the seventies. Also another regional populism can be found in Eastern Europe and Africa. In the epistemological field, populism has been studied from different perspectives, and one of these is the structuralist one. Mainly developed for Latin American cases, in this perspective, populism is associated with the development of some countries that live in a state of social exclusion. Another is an exclusively economic approach which is focused on excessive public expenditure and finding monetarist solutions to social problems. There are also political approaches that have a charismatic leader with broad social support as a central figure whose main characteristic is the use of neoliberal policies. It is possible to recognize as well other approaches in which populism is seen as party organization; or as a political style, among others. Another epistemological approach asserts that populism is not a structure, but a discourse. Thus, populism has been understood as an ideology or even as a syndrome. Nowadays three main strands of research can be identified: post-Marxist theory, quantitative approach, and a hybrid analysis that combines quantitative criteria with a qualitative discourse analysis.